Lymphocytes from rheumatoid arthritis patients have elevated levels of intracellular peroxiredoxin 2, and a greater frequency of cells with exofacial peroxiredoxin 2, compared with healthy human lymphocytes - Szabó-Taylor, Katalin É.; Eggleton, Paul; Turner, Carly A.L.; Faro, M. Letizia Lo; Tarr, Joanna M.; Tóth, Sára; Whiteman, Matt; Haigh, Richard C.; Littlechild, Jennifer A.; Winyard, Paul G. (The international journal of biochemistry & cell biology, 2012)
Peroxiredoxin 2 has immune regulatory functions, but its expression in human peripheral blood lymphocytes and levels in extracellular fluid in healthy subjects and rheumatoid arthritis patients are poorly described. In the present study, the median intracellular peroxiredoxin 2 protein content of lymphocytes from rheumatoid arthritis patients was more than two-fold higher compared with healthy subjects’ lymphocytes. Intracellular peroxiredoxin 3 levels were similar in healthy and rheumatoid arthritis lymphocytes. Flow cytometry detected peroxiredoxin 2 on the surface of ca. 8% of T cells and ca. 56% of B cells (median % values) of all subjects analyzed. Exofacial thioredoxin-1 was also observed. In the total lymphocyte population from rheumatoid arthritis patients, few cells (median, 6%) displayed surface peroxiredoxin 2. In contrast, a significantly increased proportion of interleukin-17+ve lymphocytes were exofacially peroxiredoxin 2+ve (median, 39%). Prdx2 was also detected in human extracellular fluids. We suggest that crucial inflammatory cell subsets, i.e. interleukin-17+ve T cells, exhibit increased exofacial redox-regulating enzymes and that peroxiredoxin 2 may be involved in the persistence of pro-inflammatory cells in chronic inflammation.